Transforming public health practice leadership and management essentials - Healey, Bernard J., 1947- (Jossey-Bass, 2011)
"How we address the challenges of the twenty-first century and improve the health of the public depends on the quality and preparedness of our public health workforce, which, in turn, depends on the relevance and quality of public health education and training. Providing an introduction to the practice of public health, this book covers the shift from management of communicable and infectious disease to management of chronic disease and shows how to manage and lead in public health organizations. The book's three sections cover issues and methods of public health, issues and methods of public health management, and issues and methods of public health leadership"--